Determination of Phenolic Composition of Tilia Tomentosa Flowers Using UPLC-ESI-MS/MS - Şeyda Kıvrak; Tolga Göktürk; İbrahim Kıvrak (International Journal of Secondary Metabolite)
Phenolic compounds, which are secondary metabolites of plants, are one of the main groups of compounds that provide antiallergic, antiinflammatory, antimicrobial, antioxidant, cardioprotective properties of medicinal and aromatic plants. These broad physiological effects that they possess lead researchers to examine the phenolic contents of plants. Tilia tomentosa Moench is one of 45 species belonging to Tiliaceae family, and the use of flowers in traditional treatment methods is quite common. Although it is well known that T. tomentosa flowers are rich in phenolics with various biological functions, there is no recent study on determination of phenolic compounds of T. tomentosa flowers using UPLC-ESI-MS/MS. In this study, firstly, T. tomentosa flowers were extracted using hexane and volatile oil fractions were separated from the plant. Distilled water:methanol (50:50) mixture was added to the remaining flower part at 40 °C and that subjected to extraction for 15 min. The obtained extract was filtered and dried in a lyophilizer at -70 °C. The residue was redissolved in a mixture of distilled water:methanol (80:20). The sample was analyzed by UPLC-MS/MS (Waters Acquity Ultra Performance LC, Xevo TQ-S MS/MS) by passing through Macherey-Nagel Chromafil Xtra PTFE-20/25 0.20 μm filters. According to the analysis results, 3,4-dihydroxybenzoic acid (66.820 mg/kg), myricetin (29.395 mg/kg), rutin (21.421 mg/kg), ferulic acid (12.334 mg/kg) and 3,4-dihydroxybenzaldehyde (10.383 mg/kg) were detected. T. tomentosa flowers have great potential to usage in industries such as food, medicine and cosmetic due to its rich content of phenolics.